Antifungal and Antibacterial Effect of Propolis: A Comparative Hit for Food-Borne Pseudomonas, Enterobacteriaceae and Fungi - Leonardo Petruzzi (Foods, 2020)
Propolis is a natural brownish resinous substance collected by honeybees (Apis mellifera), with a documented bioactivity against many microorganisms. In this study, the activity of propolis was investigated using some strains of Pseudomonas spp., Enterobacteriaceae, Lactobacillus plantarum, yeasts (Saccharomyces cerevisiae and Debaryomyces hansenii) and Fusarium oxysporum. Two approaches were used (a modified microdilution protocol and viable count), and the microorganisms were inoculated at two levels (low or high inoculum). The antimicrobial effect of propolis relies upon several factors, like the kind of microorganisms (for example S. cerevisiae was more resistant than D. hansenii, while Lactobacillus plantarum was never affected), the cell concentration (at high inoculum higher amounts of propolis were required for an antimicrobial action), and the mode of action (a delay of growth rather than a complete inhibition). The results of this paper point out, for the first time, the antimicrobial activity of propolis against some spoilers, with a focus on the possible effect; thus, they could be the background to designing an effective tool to prolong the shelf life of foods.